Comprehensive Analysis Identified Mutation-Gene Signature Impacts the Prognosis Through Immune Function in Hepatocellular Carcinoma - Lin, Zhuo; Xu, Qian; Song, Xian; Zeng, Yuan; Zeng, Liuwei; Zhao, Luying; Xu, Jun; Miao, Dan; Chen, Zhuoyan; Yu, Fujun (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is a life-threatening and refractory malignancy with poor outcome. Genetic mutations are the hallmark of cancer. Thus far, there is no comprehensive prognostic model constructed by mutation-gene transcriptome in HCC. The prognostic value of mutation-gene signature in HCC remains elusive. Methods: RNA expression profiles and the corresponding clinical information were recruited from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. The least absolute shrinkage and selection operator (LASSO) Cox regression analysis was employed to establish gene signature. Kaplan-Meier curve and time-dependent receiver operating characteristic curve were implemented to evaluate the prognostic value. Wilcoxon test was performed to analyze the expression of immune checkpoint genes, cell cycle genes and tumor drug resistance genes in different risk groups. Finally, quantitative real-time PCR (qRT-RCR) and immunohistochemistry (IHC) were performed to validate the mRNA and protein expression between HCC and adjacent non-tumorous tissues in an independent cohort. Results: A prognostic model consisting of five mutated genes was established by LASSO Cox regression analysis. The prognostic model classified patients into high- and low-risk groups. Compared with low‐risk group, patients in high‐risk group had significantly worse survival results. The prognostic model can accurately predict the overall survival of HCC patients, and predict overall survival more accurately when combined with stage. Furthermore, the immune checkpoint genes, cell cycle genes and tumor drug resistance genes were higher expressed in high-risk group compared in low-risk group. In addition, the expression level of prognostic signature genes was validated in an independent sample cohort, which was consistent with RNA sequencing expression in the TCGA database. Conclusion: The prediction model of HCC constructed using mutation-related genes is of great significance for clinical decision making and the personalized treatment of patients with HCC.